Ensuring safe docking maneuvers on floating platform using Nonlinear Model Predictive Control (NMPC) - Gatti, Federico (Luleå tekniska universitet, Institutionen för system- och rymdteknik, 2024)
Docking maneuvers are a relevant part of the modern space mission, requiring precision and safety to ensure the success of the overall mission. This thesis proposes using a non-linear Model Predictive Control (MPC) as a controller with various constraints to ensure safe docking maneuvers for a satellite. This was done in MATLAB using as a model for the satellite the Sliders used by the Robotics Lab at Luleå University of Technology (LTU). The controller was tested first on the MATLAB model and then briefly on hardware.The main objective of this thesis is to develop and implement an MPC-based control strategy to achieve safe docking maneuvers between two satellites. Great attention has been paid to implementing constraints, such as collision avoidance, and hardware constraints, such as thrust limits, to ensure the safety and reliability of the process.Through the MATLAB simulations, it was possible to indicate that the introduced constraints contribute significantly to the safe execution of docking maneuvers, preventing collisions, andoptimizing fuel usage. The controller successfully adapts to unforeseen disturbances and uncertainties in real-time, showcasing its robustness and reliability in dynamic space environments.The hardware simulations have shown that the controller operates as expected but needs further tuning to adapt to the hardware uncertainties.In conclusion, this thesis comprehensively explores MPC-based control strategies with constraints for space docking maneuvers. The positive results underscore this approach’s potential to ensure the safety and reliability of future space missions, opening avenues for further research and application in autonomous space systems.